Iron superoxide dismutases in eukaryotic pathogens: new insights from apicomplexa and trypanosoma structures - Phan, Isabelle Q. H.; Davies, Douglas R.; Moretti, Nilmar Silvio; Shanmugam, Dhanasekaran; Cestari, Igor; Anupama, Atashi; Fairman, James W.; Edwards, Thomas E.; Stuart, Kenneth; Schenkman, Sergio; Myler, Peter J. (Acta Crystallographica Section F-Structural Biology Communications, 2015)
Prior studies have highlighted the potential of superoxide dismutases as drug targets in eukaryotic pathogens. This report presents the structures of three iron-dependent superoxide dismutases (FeSODs) from Trypanosoma cruzi, Leishmania major and Babesia bovis. Comparison with existing structures from Plasmodium and other trypanosome isoforms shows a very conserved overall fold with subtle differences. In particular, structural data suggest that B. bovis FeSOD may display similar resistance to peroxynitrite-mediated inactivation via an intramolecular electron-transfer pathway as previously described in T. cruzi FeSOD isoform B, thus providing valuable information for structure-based drug design. Furthermore, lysine-acetylation results in T. cruzi indicate that acetylation occurs at a position close to that responsible for the regulation of acetylation-mediated activity in the human enzyme.
Keywords: Apicomplexa; iron superoxide dismutase; Trypanosoma